2004
DOI: 10.1091/mbc.e04-05-0375
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Response of Yeast to Aflatoxin B1: Recombinational Repair InvolvingRAD51andRAD1

Abstract: The potent carcinogen aflatoxin B 1 is a weak mutagen but a strong recombinagen in Saccharomyces cerevisiae. Aflatoxin B 1 exposure greatly increases frequencies of both heteroallelic recombination and chromosomal translocations. We analyzed the gene expression pattern of diploid cells exposed to aflatoxin B 1 using high-density oligonucleotide arrays comprising specific probes for all 6218 open reading frames. Among 183 responsive genes, 46 are involved in either DNA repair or in control of cell growth and di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
43
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 65 publications
6
43
0
Order By: Relevance
“…3) also suggests that both NER and HRR act on one or more common substrates. These results are consistent with the involvement of Rad1, required in NER (81), in the repair of AFB 1 -induced DNA damage via recombinational repair (48). In the absence of the two repair pathways, these AFB 1 -induced DNA lesions are channeled into a mutagenic repair pathway mediated by REV3.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…3) also suggests that both NER and HRR act on one or more common substrates. These results are consistent with the involvement of Rad1, required in NER (81), in the repair of AFB 1 -induced DNA damage via recombinational repair (48). In the absence of the two repair pathways, these AFB 1 -induced DNA lesions are channeled into a mutagenic repair pathway mediated by REV3.…”
Section: Discussionsupporting
confidence: 86%
“…Both pathways are also involved in the repair of UV damage (8). Our data are also consistent with the loss of AFB 1 -induced recombination in a diploid rad51 mutant transformed with human CYP1A1 (48). It could be that replication forks collapse when encountering AFB 1 -DNA adducts, leaving single strands whose repair is likely to be dependent on Rad51 (19).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The expression of the RAD1 gene, the product of which plays a crucial role in the repair of DNA double-strand breaks by homologous recombination, was shown to be downregulated in response to oxidative stimulus in AMD patients (Strunnikova et al 2005). The coordinated involvement of Rad51 and Rad1 in recombinational repair of DNA damage implicates the potential role of RAD51-dependent DNA repair in circumstances of elevated oxidative reaction species (Keller-Seitz et al 2004).…”
Section: Discussionmentioning
confidence: 98%
“…Several of these pathways are also involved in tolerance to aflatoxin B 1 in mammalian cells [9]. Additionally, microarray experiments on aflatoxin B 1 treated yeast cells expressing CYP1A2 showed that expression of genes involved in DNA synthesis and repair, cell cycle regulation, or protein degradation and synthesis was significantly altered [25,130].…”
Section: Cytochrome P450-related Toxicity In Yeastmentioning
confidence: 99%